1995
DOI: 10.1016/0885-3924(95)00065-7
|View full text |Cite
|
Sign up to set email alerts
|

Occult infection as a cause of hip pain in a patient with metastatic breast cancer

Abstract: A 39-year-old woman with breast cancer metastatic to bone presented with acute hip pain marginally responsive to escalating doses of opioid analgesics. Pathologic pelvic fractures were present and there were minimal clinical indicators of infection, but the severity and intractable nature of the pain prompted further investigation. Computed tomography revealed a pelvic abscess. Antibiotic therapy and drainage of the abscess resulted in markedly improved pain control, decreased analgesic requirements, and impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Fabiszewski et al 5 reported that treatment of fever with antibiotics did not alter the outcome of fever in institutionalized advanced Alzheimer patients, while some authors have reported improved pain control with the use of antimicrobials in a small number of patients with acute systemic or local infections. [6][7][8] Patient survival in this study was not affected by the presence of infection or the use of antimicrobials. In the study by Vitetta et al, 1 patients with documented infections had a longer median survival.…”
Section: Discussionmentioning
confidence: 78%
“…Fabiszewski et al 5 reported that treatment of fever with antibiotics did not alter the outcome of fever in institutionalized advanced Alzheimer patients, while some authors have reported improved pain control with the use of antimicrobials in a small number of patients with acute systemic or local infections. [6][7][8] Patient survival in this study was not affected by the presence of infection or the use of antimicrobials. In the study by Vitetta et al, 1 patients with documented infections had a longer median survival.…”
Section: Discussionmentioning
confidence: 78%
“…MacKey and MacDonald described a patient in which a large psoas abscess resulted in severe abdominal pain. 42 Antibiotic therapy and surgical drainage resulted in good symptom control.…”
Section: Discussionmentioning
confidence: 99%
“…Green et al ont décris un contrôle efficace des symptômes liés aux infections chez 2 patients atteints de cancer qui ont été traités par antibiotiques [24]. Par ailleurs, Mac Key et Mac Donald ont décris un patient atteint d'un abcès du muscle psoas, et qui souffrait de violentes douleurs abdominales [25]. L'antibiothérapie et le drainage chirurgical ont eu comme effet un soulagement rapide du patient.…”
Section: Efficacité De L'antibiothérapieunclassified